Incidence of influenza during pregnancy and association with pregnancy and perinatal outcomes in three middle-income countries: a multisite prospective longitudinal cohort study. Issue 1 (January 2021) - Dawood, Fatimah S; Kittikraisak, Wanitchaya; Patel, Archana; Rentz Hunt, Danielle; Suntarattiwong, Piyarat; Wesley, Meredith G; Thompson, Mark G; Soto, Giselle; Mundhada, Shailendra; Arriola, Carmen S; Azziz-Baumgartner, Eduardo; Brummer, Tana; et al.
Summary: Background: Influenza vaccination during pregnancy prevents influenza among women and their infants but remains underused among pregnant women. We aimed to quantify the risk of antenatal influenza and examine its association with perinatal outcomes. Methods: We did a prospective cohort study in pregnant women in India, Peru, and Thailand. Before the 2017 and 2018 influenza seasons, we enrolled pregnant women aged 18 years or older with expected delivery dates 8 weeks or more after the season started. We contacted women twice weekly until the end of pregnancy to identify illnesses with symptoms of myalgia, cough, runny nose or nasal congestion, sore throat, or difficulty breathing and collected mid-turbinate nasal swabs from symptomatic women for influenza real-time RT-PCR testing. We assessed the association of antenatal influenza with preterm birth, late pregnancy loss (≥13 weeks gestation), small for gestational age (SGA), and birthweight of term singleton infants using Cox proportional hazards models or generalised linear models to adjust for potential confounders. Findings: Between March 13, 2017, and Aug 3, 2018, we enrolled 11 277 women with a median age of 26 years (IQR 23–31) and gestational age of 19 weeks (14–24). 1474 (13%) received influenza vaccines. 310 participants (3%) had influenza (270 [87%] influenza A and 40 [13%] influenza B). Influenza incidences weighted by the population of women of childbearing age in each study country were 88·7 per 10 000 pregnant woman-months (95% CI 68·6 to 114·8) during the 2017 season and 69·6 per 10 000 pregnant woman-months (53·8 to 90·2) during the 2018 season. Antenatal influenza was not associated with preterm birth (adjusted hazard ratio [aHR] 1·4, 95% CI 0·9 to 2·0; p=0·096) or having an SGA infant (adjusted relative risk 1·0, 95% CI 0·8 to 1·3, p=0·97), but was associated with late pregnancy loss (aHR 10·7, 95% CI 4·3 to 27·0; p<0·0001) and reduction in mean birthweight of term, singleton infants (−55·3 g, 95% CI −109·3 to −1·4; p=0·0445). Interpretation: Women had a 0·7–0·9% risk of influenza per month of pregnancy during the influenza season, and antenatal influenza was associated with increased risk for some adverse pregnancy outcomes. These findings support the added value of antenatal influenza vaccination to improve perinatal outcomes. Funding: US Centers for Disease Control and Prevention. Translations: For the Thai, Hindi, Marathi and Spanish translations of the abstract see Supplementary Materials section.